Analysis of Students’ Reading Comprehension Ability at an Islamic-based Elementary School in Klaten, Indonesia - Wahyuningtyas, Utami; Zainuddin, Almuntaqo (Universitas Ahmad Dahlan, 2025)
This study analyzes students' reading comprehension skills, especially highlighting and summarizing skills in grade 5 students of MI Muhammadiyah Srebegan (an Islamic-based Elementary School). This study uses a qualitative research method. Data collection techniques in this study consist of 3 techniques: tests, interviews, and observations. The data analysis used in this study uses triangulation. The subjects of the study were homeroom teachers and 30 grade 5 students. Based on the study's results, it can be concluded that all grade 5 students of MI Muhammadiyah Srebegan, Klaten, are fluent or able to read. Some grade 5 students of MI Muhammadiyah Srebegan are skilled at highlighting and summarizing reading texts. There are some students whose reading comprehension skills are still low. Regarding reading comprehension skills, the teacher tries to ensure that grade 5 students always read texts to improve their reading comprehension skills.